Beyond conflict: the role of life-domain enrichment for expatriates - Kempen, Regina; Jöns, Ingela (International journal of human resource management, 2015)
The employment of expatriates has become an increasingly important part of professional business careers, and thus factors that influence the success of international assignments have increased in importance. Among these factors, the interaction of life domains plays an important role. This study applied recent advancements in the domestic literature on the interplay between different life domains to the expatriates' situation. These advancements affect the scope of the life domains considered, the different directions of interactions between life domains and the inclusion of a positive perspective on the interplay. Among a sample of expatriates in the development cooperation sector on four continents, this study investigated the impact of life-domain enrichment on expatriates' assignments. Results showed that life-domain enrichment accounted for variance in job satisfaction, turnover intentions and accomplishment of role-related expectations, beyond what was accounted for by life-domain conflict. These findings underscore the need to consider life-domain variables and processes when examining expatriate adjustment. Implications for training and support of expatriates are discussed.